Ung Dung Phuong phap phan tich hinh anh de danh gia xoi mon dat - Van Thiet, N.; Pomel, S.; Pham Quang, H.; Tran Duc Toan; Orange, Didier (2008)
Optical analysing technique is recently developed for soil erosion evaluation with high resolution digital camera with use of software programs such as Optilab Pro. This paper reports results from a study in Dong Cao (Luong Son, Hoa Binh, Vietnam). Results were obtained on digital images analysis from two Sub-Catchment (W2, W3) with 28 plots. The results indicated a range of soil loss of 937 to 1553 kg per ha for W2 and 1225 to 2050 kg per ha for W3. The difference of soil erosion was mainly due to the difference of cover crops. Linear regression was made and it showed a very closed correlation between conventional and optical methoda in soil erosion study. In terms of the absolute value, optical method showed a higher value than the conventional one. The reason may be due to the optical theoretical method calculated the maximum soil moved from the site (eroded) while the conventional experimental method measured the soil erosion collected in experiment weir. In long term, with more data, this optical method should be further checked and recalibrated for other types of soil covers and soil topography for the use in larger scales.